Students’ Knowledge of Sexually Transmitted Infections (STIs) - Cahya Kusuma Dewi; Tina Mawardika (CV. Global Health Science Group, 2026)
Sexually Transmitted Infections (STIs) are reproductive health problems that remain a global concern, particularly among young adults, including university students. Lack of knowledge regarding STIs may increase the risk of engaging in risky sexual behaviors, which can have long-term impacts on reproductive health. Students, as individuals in the productive age group, need to have adequate understanding of STIs, including definitions, modes of transmission, symptoms, complications, and prevention as part of promotive and preventive health efforts. This study aimed to describe the level of students’ knowledge regarding the transmission of Sexually Transmitted Infections (STIs). This study used a descriptive analytic design with a cross-sectional approach. The population consisted of all undergraduate nursing students at Ngudi Waluyo University, class of 2025, totaling 493 students. The sample comprised 221 respondents selected using purposive sampling. Data were collected using the Sexually Transmitted Disease Knowledge Questionnaire (STD-KQ), which has been tested for validity and reliability. Data analysis was performed using univariate analysis. The results showed that the majority of respondents had a low level of knowledge regarding STIs, with 104 respondents (47.1%). Most university students have a low level of knowledge regarding sexually transmitted infections.